How Does Support by the Organization Decrease Employee’s Intention to Leave? - Novianthi Dian Purnamawati; Debora Eflina Purba (Jurnal Ilmu Perilaku, 2018)
This study aims to investigate the mediating effect of affective commitment in the relationship between perceived organizational support and turnover intention. Data were collected using paper-and-pencil survey on inbound Customer Service Officers (CSO) of a Contact Center X in Jakarta operating in service of electricity needs by phone calls (N = 96). Data were analyzed using Hayes PROCESS macro on SPSS software. Results showed that perceived organizational support was negatively related to turnover intention and positively related to affective commitment. Results also showed that affective commitment was negatively correlated with turnover intention. The mediation analysis showed that affective commitment fully mediated the relationship between perceived organizational support and turnover intention. The theoretical and practical implications of the study were further discussed.